Dexmedetomidine Injection during Strabismus Surgery Reduces Emergence Agitation without Increasing the Oculocardiac Reflex in Children: A Randomized Controlled Trial - Song, In-Ae (PLoS One, 2016)
OBJECTIVE: Dexmedetomidine is known to reduce the incidence of emergence agitation, which is a common complication after inhalational anesthesia like sevoflurane or desflurane in children. However, the dose of dexmedetomidine used for this purpose is reported variously and the most effective dose is not known. In this study, we tried to find the most effective dose of dexmedetomidine to reduce the incidence of emergence agitation in children undergoing strabismus surgery without the complications like oculocardiac reflex (OCR) or postoperative vomiting. METHODS: We randomized 103 pediatric patients aged 2–6 years and undergoing elective strabismus surgery into four groups. Anesthesia was induced with sevoflurane and maintained with desflurane. At the start of induction, dexmedetomidine, delivered at 0.25, 0.5, or 1 μg/kg, or saline was infused intravenously in the D0.25, D0.5, D1 groups, respectively. The primary outcome measure was the incidence of emergence agitation and the secondary outcome measure was the incidence of intraoperative OCR, postoperative vomiting, and desaturation events. RESULTS: The incidence of emergence agitation was 60, 48, 44, and 21% (P = 0.005) and the incidence of intraoperative OCR was 36, 36, 36, and 37% (P = 0.988) in the control, D0.25, D0.5, and D1 groups, respectively. And, postoperative vomiting rate and desaturation events were low in the all groups. CONCLUSION: Dexmedetomidine decreased the incidence of emergence agitation without increasing intraoperative oculocardiac reflex. Dexmedetomidine delivered at 1 μg/kg was more effective at reducing emergence agitation than lower doses in children undergoing strabismus surgery under desflurane anesthesia. TRIAL REGISTRATION: Clinical Research Information Service KCT0000141